2010
DOI: 10.1007/s10802-010-9468-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depressive Symptoms and Child Social Preference During the Early School Years: Mediation by Maternal Warmth and Child Emotion Regulation

Abstract: This longitudinal study examined processes that mediate the association between maternal depressive symptoms and peer social preference during the early school years. Three hundred and fifty six kindergarten children (182 boys) and their mothers participated in the study. During kindergarten, mothers reported their level of depressive symptomatology. In first grade, teachers rated children’s emotion regulation at school and observers rated the affective quality of mother-child interactions. During second grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
0
17
0
3
Order By: Relevance
“…Low-income mothers tend to be more stressful and to produce children with poor emotion regulation (Blandon, Calkins, Keane & O'Brien, 2008;Lengua et al, 2008;Kam et al, 2011). This current study shows that mothers' employment status correlates with maternal stress.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Low-income mothers tend to be more stressful and to produce children with poor emotion regulation (Blandon, Calkins, Keane & O'Brien, 2008;Lengua et al, 2008;Kam et al, 2011). This current study shows that mothers' employment status correlates with maternal stress.…”
Section: Discussionmentioning
confidence: 51%
“…Prior studies attempted to prove the correlation between maternal negative emotions, such as stress or depression, and children's low emotion regulation (Blandon, Calkins, Keane & O'Brien, 2008;Lengua et al, 2008;Kam et al, 2011). However, a contradictory result is shown by Choe, Olson, and Sameroff (2013) who found that maternal stress is mediated by inductive discipline and maternal warmth and does not correlate directly with children's emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Auch können sie sich gut selbst regulieren (Eisenberg et al 1993;Kam et al 2011), neigen nicht zu starken negativen Gefühlen und haben tendenziell relativ viele erwiderte, wenig konfliktreiche Freundschaften (Litwack et al 2012). Beliebte Kinder sind insgesamt meist weniger aggressiv als abgelehnte Kinder , aber im Vergleich zu den als durchschnittlich klassifizierten Kindern (die bei soziometrischen Gruppenurteilen sowohl einige positive als auch einige negative Nominierungen erhalten) sind sie nur in Bezug auf Aggressionen, die mit allgemeiner Wut, Rachsucht oder Genugtuung beim Verletzen anderer zusammenhängen, weniger aggressiv ).…”
Section: Beliebte Kinderunclassified
“…Die Mütter von sozial kompetenten und beliebten Kindern sprechen beispielsweise häufiger als die Mütter weniger kompetenter Kinder mit ihrem Kind über Gefühle und sind dabei im Allgemeinen warmherzig kontrollierend, benutzen eine positive Wortwahl, argumentieren logisch und geben Erklärungen Kam et al 2011;McDowell und Parke 2009;Updegraff et al 2010 (Feldman und Masalha 2010). Diese Zusammenhänge können darauf beruhen, dass die Erziehung die Selbstregulierung der Kinder fördert (Eiden et al 2009;Eisenberg et al 2005;Kam et al 2011).…”
Section: Peerbeziehungen Und Die Qualität Der Elternkindinteraktionenunclassified
See 1 more Smart Citation